SYTACTIC STRATEGIES IN THE CULTURAL HEADLINES OF AL-MISRY AL-YOUM: A TRANSFORMATIONAL-GENERATIVE ANALYSIS - Syaifullah; Aura Kholifatunnisa (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
Media headlines are not merely informative statements but compact linguistic constructions laden with ideological meaning. This study analyzes fifteen cultural headlines from Al-Misry Al-Youm (April–June 2025) using Noam Chomsky’s transformational- generative grammar framework (1965, 1975). This approach posits that surface structures are derived from deeper semantic structures through various syntactic transformations. Employing a qualitative-descriptive method and documentation technique, the study identifies dominant patterns such as ellipsis, inversion, and nominalization. The findings reveal that these syntactic forms serve not only to economize language but also as rhetorical strategies for framing cultural representation, institutional authority, and embedded social values. The discussion emphasizes that each syntactic transformation carries pragmatic and ideological functions that influence how readers interpret cultural messages. Thus, headlines are not neutral structures but deliberate discursive practices that shape cultural and ideological realities.